Papel protetor das citocinas IL-9/IL-10 em lesões perriradiculares humanas - Lucas Moreira Maia (2017)
This study aims to identify the gene expression of a new group of T lymphocytes, Th9 cells, characteristically responsible for producing IL-9 in the periradicular tissues of individuals with endodontic infections submitted to routine endodontic therapy, in the presence and absence of infection as well as the cytokines TNF-, IL-1. IL-9, INF- and IL-10 and CCL-2 / MCP-1 and CCR-6 chemokines in the periapical interstitial fluid of human root canal infections. Samples were collected immediately after cleaning and formatting procedures and 7 days later (after reduction of intracanal microbial load) to characterize the expression of these genes. Real-time polymerase chain reaction demonstrated significantly higher levels of IL-1, IL-9, INF-, TNF- and IL-10 markers at day 7 compared to day 0. In turn, the CCL-2 / MCP-1 and CCR-6 chemokines and IL- 17A cytokine showed no significant differences in mRNA expression between the 2 periods analyzed. In analyzing the clinical variation after endodontic therapy on periapical immune status, this study demonstrated that the cytokine and chemokinemediated proinflammatory response appears to be modulated in a IL-10 / IL-9 dependent manner.